Bulleh Shah’s Anti-Orthodox Views on Self-Purification and Their Implications for Social Reforms in Punjabi Society - Abbas, Qamar (Pakistan Journal of Humanities and Social Sciences, 2023)
Bulleh Shah is regarded as a social critic and reformer, though he was not a conventional preacher, but he was a true critic of his contemporary society. Sufis aimed at ethical character reformation of the society. This article discusses the moral and ethical situation in Punjabi society of Bulleh Shah’s time and his Sufi philosophy for social reforms. Bulleh Shah reflected on the social situation of his time in his poetry. This article relates Bulleh Shah’s views regarding social reforms to the concurrent social issues in Punjabi society. Bulleh Shah focused on the real character and criticized hypocrisy and duality in pursuit of social, political, and religious aims. Punjab remained a gateway for the invading forces in India. So, the social structure in Punjab remained complex with a clear distinction between the privileged and underprivileged classes. The exploitative social order inspired pride and hollow show among the upper elite and inferiority sentiments among the least privileged classes. Bulleh Shah’s philosophy for self-purification and salvation focuses on the negation of self-pride to achieve harmony with nature and humanity in general. Punjab was not a land of homogeneous class structure, race, and religion. Here was a merger of various cultures, and people belonged to different religions. These differences were so obvious that it was difficult to extract the uniform principle on which the Punjabi identity could be constructed. Religion, caste structure, sect, and biradari all played important roles in constructing Punjabi identity. These were the critical issues of concern for the intelligentsia of that time.